Amphoteric self-supporting single-ion polymer electrolyte diaphragm as well as preparation method and application thereof
By doping zwitterionic compounds in the polymer electrolyte membrane, the dissociation and conduction efficiency of lithium ions are improved, the problem of low conductivity in the prior art is solved, and more efficient lithium ion conduction and the effect of inhibiting lithium dendrites is achieved.
Patent Information
- Application Number
- CN202311101004.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The current polymer electrolyte products have low conductivity, which affects their application in the field of lithium batteries.
Zwitterionic compounds are used to physically dopate self-supported single-ion polymer electrolyte membranes, introducing zwitterionic effects to improve ionic conductivity.
Doping zwitterionic materials significantly improves the ionic conductivity of the polymer electrolyte membrane, improves the dissociation and conduction efficiency of lithium ions, and inhibits the formation of lithium dendrites.
Smart Images

Figure SMS_2 
Figure SMS_5 
Figure SMS_10
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery material preparation, and in particular relates to an amphoteric self-supporting single-ion polymer electrolyte membrane and a preparation method and application thereof. Background Art
[0002] Although the use of lithium metal as anode can be traced back to the birth of lithium batteries, safety issues caused by lithium dendrites have hindered its commercial application. It was not until the discovery of graphite that the low-potential insertion / release of lithium became possible, and the prototype of the commercial lithium-ion secondary battery was formally established, that is, graphite as anode, LiCoO2 as cathode, and LiPF6 dissolved in carbonate solvent as electrolyte.
[0003] With the growing demand for high-energy-density lithium-ion secondary batteries, metallic lithium has attracted widespread attention for its high capacity. Lithium dendrites are formed by the irregular deposition of lithium during the charging process. When they are deposited to a certain shape and pierce the diaphragm, the battery cell will have an internal short circuit. At present, the research on the growth mechanism of lithium dendrites is not thorough enough. However, due to its special molecular structure, single-ion electrolyte materials only allow single conduction of lithium ions, which can minimize concentration polarization and thus inhibit the formation of lithium dendrites. Self-supporting single-ion polymer electrolytes can directly form films and provide lithium ions as a lithium source without the use of polymer binders, thereby increasing the lithium ion content per unit area, avoiding the increase in the distance between ion groups caused by the addition of PVDF or PVDF-HFP to weaken the electrostatic force, reduce the tendency to crystallize, and reduce the lithium ion solid content and uniformity problems.
[0004] Self-supporting single-ion gel polymer electrolytes are synthesized by grafting sulfonimide groups onto polymer chains. However, due to the low distribution of negative charges in these polyanions, the dissociation of lithium ions from the polyelectrolyte backbone is very limited, resulting in low ionic conductivity even at high temperatures, a feature that greatly affects its application in the field of lithium batteries. Summary of the invention
[0005] The technical problem to be solved by the present invention is to address the problem of low conductivity of existing polymer electrolyte products, and to provide a zwitterionic self-supporting single-ion polymer electrolyte membrane and a preparation method and application thereof, wherein the self-supporting single-ion polymer electrolyte membrane is physically doped with zwitterionic compounds to introduce a zwitterionic effect to improve ionic conductivity.
[0006] To achieve the above object, the present invention adopts the following technical solution: an amphoteric self-supporting single-ion polymer electrolyte membrane, wherein the membrane is made by physically doping a zwitterionic compound with a self-supporting single-ion polymer.
[0007] Furthermore, the molecular structure of the zwitterionic compound contains two ions of different charges, which are covalently bonded in one molecule and are electrically neutral as a whole. The cations in the zwitterionic molecule include but are not limited to quaternary ammonium or quaternary phosphonium; the anions include but are not limited to The molecular weight of zwitterionic compounds is between 200 and 2000.
[0008] Furthermore, the molecular structure of the zwitterionic compound is shown in Formula 1 or Formula 2:
[0009]
[0010] Wherein R2 is a quaternary ammonium or quaternary phosphonium group, R1, R3 are n1, n2 are 1, 2, 3, 4, 5.
[0011] Furthermore, the self-supporting single-ion polymer is a polymer lithium salt, the main chain of which is polybenzimidazole, polyethylene maleic anhydride, polyethylene, polyamide or polyether, and the side chain is lithium sulfonimide, lithium phosphate, lithium borate or lithium perchlorate.
[0012] Furthermore, the polymer lithium salt structural formula is:
[0013]
[0014] Furthermore, the mass of the zwitterionic compound accounts for 10% to 40% of the mass of the self-supporting single ionic polymer.
[0015] A preparation method according to the above-mentioned amphoteric self-supporting single-ion polymer electrolyte membrane comprises the following steps: preparing the amphoteric self-supporting single-ion polymer membrane by physical doping: taking a self-supporting single-ion polymer and a zwitterionic compound in an organic solvent, fully heating and stirring until completely dissolved, to obtain a uniformly dispersed polymer electrolyte coating slurry; evenly scraping the above-mentioned coating slurry on the surface of a substrate, after sufficient drying, the electrolyte membrane is uniformly formed into a film and then demolded to obtain an amphoteric self-supporting single-ion polymer membrane.
[0016] Furthermore, the organic solvent is anhydrous N-methylpyrrolidone, acetone, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.
[0017] A use of the above-mentioned amphoteric self-supporting single-ion polymer electrolyte membrane in a battery.
[0018] Compared with the prior art, the amphoteric self-supporting single-ion polymer electrolyte membrane of the present invention has the following beneficial effects:
[0019] 1. The present invention greatly improves the ionic conductivity of the polymer electrolyte membrane by doping with zwitterionic materials. The positive and negative charges of zwitterionic materials produce a dipole effect through dipole rotation. The addition of zwitterionic materials can increase the dielectric constant of the electrolyte, weaken the electrostatic attraction between lithium ions and polyanions in the molecular structure of the polymer electrolyte, and promote the dissociation of lithium ions, thereby increasing the number of effective charge carriers to improve ionic conductivity.
[0020] 2. The present invention synthesizes a novel zwitterionic material MeImPS, which is doped with PBI-g-LiPSI to form a polymer electrolyte with 10 -3 The ionic conductivity at the S / cm level is far superior to existing polymer electrolytes.
[0021] 3. The polymer electrolyte synthesized in the present invention has a high molecular polymer structure. During the electrochemical reaction, its anions are relatively fixed, and single-ion conduction of lithium ions can be achieved, thereby achieving uniform deposition of lithium ions on the negative electrode surface and inhibiting the formation of lithium dendrites.
[0022] 4. In the present invention, all the membrane components are electrolyte components, and no additional binder is needed, so a self-supporting electrolyte membrane with qualified mechanical properties can be prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The H-NMR spectra of the material prepared in Example 1 are as follows: (a) NaCPSI, (b) MeIm, and (c) MeImPSI.
[0024] Figure 2 The H-NMR spectra of the materials prepared in Example 1 are as follows: (a) NaCPSI, (b) PBI, and (c) PBI-g-LiPSI. Figure 3 These are graphs showing the ionic conductivity of the membrane prepared in Example 1 (a and c are the temperature variation curves of the ionic conductivity of the self-supporting single ion membrane with a doping ratio of 0% and 25wt%; b and d are the lithium ion migration numbers tested by measuring the relationship between the steady-state current and the AC impedance).
[0025] Figure 4 is the Me2(LiPSI)N(PSI) of Example 2 1 H NMR spectrum.
[0026] Figure 5 is the LiCPSI and Me2(LiPSI)N(PSI) of Example 2 7 Li NMR spectrum.
[0027] Figure 6These are the performance diagrams of the button cells prepared in Example 2: (a) rate performance of the PP diaphragm button cell, (b) rate performance of the membrane electrode button cell; (c) charge and discharge curves of the PP diaphragm button cell at different rates, (d) charge and discharge curves of the membrane electrode button cell at different rates. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiment of the present application will be clearly and completely described below in combination with the embodiment of the present application. Obviously, the described embodiment is only a part of the embodiment of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0029] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present application and the above-mentioned drawings are intended to cover non-exclusive inclusions. For example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or apparatuses.
[0030] Specifically, in Example 1 of the embodiment of the present invention, a new zwitterionic material MeImPS was synthesized. After doping with PBI-g-LiPSI, this material can significantly improve the ionic conductivity of the electrolyte membrane.
[0031] The mechanism of improving the ionic conductivity of the polymer electrolyte membrane by doping with zwitterionic materials in this embodiment can be explained as follows: the positive and negative charges of the zwitterionic materials produce a dipole effect through dipole rotation, and their addition can increase the dielectric constant of the electrolyte, weaken the electrostatic attraction between lithium ions and polyanions in the molecular structure of the polymer electrolyte, and promote the dissociation of lithium ions, thereby increasing the number of effective charge carriers to improve ionic conductivity.
[0032] Example 1
[0033] (1) Synthesis of zwitterionic MeImPSI materials:
[0034] 1. Take 1-methylimidazole (3.6 mmol, 0.31 g), dissolve it in 20 mL of anhydrous acetonitrile, replace it with argon three times, and stir it at room temperature for 12 h to obtain a colorless transparent solution A.
[0035] 2. Take the condenser and 50mL two-necked flask, place them in an oven at 110℃, preheat for 1h, build the device from bottom to top while hot, and wrap it with tin foil. Use argon to ventilate 3 times, wait for the device to cool slightly, add 20mL of anhydrous acetone, then add NaCPSI (3mmol, 0.93g), stir until NaCPSI dissolves, add NaI (5mmol, 0.76g) in complete light avoidance, use argon to replace 3 times, reflux at 85℃ for 24h, use tin foil to avoid light, and use curtains to avoid light. After cooling, let it stand for B, and white substance remains.
[0036] The supernatant of B was drawn into another 50 mL flask (wrapped in tin foil) using a syringe wrapped in tin foil, and the acetone was evaporated as much as possible in the absence of light, and the acetone was removed by reduced pressure distillation.
[0037] Then, A was added to B, and 10 mL of anhydrous acetonitrile was added, and the mixture was replaced with argon gas and reacted at 85°C for 24 h. After the reaction, the mixture was cooled to room temperature.
[0038] Pour 20 mL of ether to precipitate the product into solids, dry it at 80° C. with forced air, and then dry it at 80° C. in a vacuum oven for 24 h to obtain a yellow solid powder, which is the zwitterionic MeImPSI material.
[0039] The reaction formula is as follows:
[0040] (a)
[0041] (b)
[0042] The synthesized materials were characterized as follows Figure 1 Figure a is the H NMR spectrum of NaCPSI, and Figure b is the H NMR spectrum of 1-methylimidazole raw material. In addition to the water peak and the peak of the internal reference deuterated DMSO reagent, there are four groups of peaks. 3.64ppm, 6.90ppm, 7.10ppm and 7.57ppm correspond to the proton hydrogen of the imidazole ring in 1-methylimidazole, respectively, with an area integration ratio of 3.04:1.05:1.03:1.00, and are marked as "dg" in turn. In Figure c, 2.22, 3.02, 4.32, 3.84, 7.71, 7.78, 7.35 and 9.13 ppm are the hydrogens on LiPSI marked as "a", "b", "c" and the hydrogens on 1-methylimidazole marked as "d", "e", "f" and "g", respectively, among which the integrated area ratios of "a", "d", "e", "f" and "g" are 1.00:1.53:0.50:0.51:0.51, indicating that NaCPSI is attached to 1-methylimidazole, that is, the amphiphilic molecule MeImPSI is successfully synthesized.
[0043] (2) Synthesis of PBI-g-LiPSI materials
[0044] 1. Take PBI polymer (2 g, 5.144 mmol), add 95 mL of anhydrous N-methylpyrrolidone (NMP), replace with argon three times, heat to 120°C and stir for 12 hours to obtain a light yellow transparent solution after complete dissolution.
[0045] 2. Add 0.35 g of LiH under argon protection and stir at 120°C for 20 h to produce a brown-yellow liquid. Cool naturally to room temperature and mark it as A.
[0046] 3. Take the condenser and 250mL two-necked flask, place them in a 110℃ oven, preheat for 1h, build the device from bottom to top while hot, and wrap it with tin foil. Replace the argon gas 3 times, and after the device is slightly cooled, add 25mL of anhydrous acetone, then add NaCPSI (17.04mmol, 6g), and stir until NaCPSI is completely dissolved.
[0047] 4. Add 90 mL of acetone (slightly turbid), add NaI (54 mmol, 8.1 g), replace with argon three times, reflux at 85°C for 24 h, and protect from light. Cool naturally to room temperature and let stand for B. White substance remains at the bottom.
[0048] 5. Use a syringe wrapped in tin foil to draw the supernatant of B into another 250 mL flask (flask wrapped in tin foil), evaporate the acetone as much as possible in the absence of light, and distill under reduced pressure to obtain NaIPSI.
[0049] 6. Then add A to B, replace with argon three times, heat to 120℃ and react for 72h. Cool naturally. Distill under reduced pressure at 120℃ and concentrate to obtain a dark brown viscous liquid.
[0050] 7. Add an appropriate amount of deionized water. If bubbles are generated, stir to remove excess LiH, then pour into a large amount of acidic (HCl, 1M) aqueous solution, stir until there are no bubbles on the liquid surface, stir ultrasonically, and precipitate a dark brown sample.
[0051] 8. Filter by suction, the filter cake is a dark brown solid, wash three times with water, acidify with (1M) HCl and stir for 72h, dark brown uniform suspension. Filter by suction, wash three times with water, take the filter cake. Lithiation for 12h does not dissolve, and brown solid is obtained.
[0052] 9. Filter with a sand core funnel and dialyze with a dialysis bag for 3 days to remove impurities. Distill under reduced pressure to remove the water solvent, dry at 80°C for 24 hours, and then vacuum dry at 100°C for 24 hours to obtain a brown solid, that is, 3.07g of polybenzimidazole grafted propylsulfonyl (trifluoromethanesulfonyl) imide lithium polymer (PBI-g-LiPSI).
[0053] The reaction is as follows
[0054] (a)
[0055] (b)
[0056] The synthesized materials were characterized as follows Figure 2 As shown, Figure a shows the H NMR spectrum of NaCPSI, and Figure b shows the H NMR spectrum of the PBI raw material. In addition to the water peak and the peak of the internal reference deuterated reagent, there are four groups of peaks. 7.33ppm, 7.77ppm, 8.30ppm and 13.0ppm correspond to the proton hydrogen on the benzene ring and nitrogen in PBI, respectively, with an area integration ratio of 1.00:1.50:1.01:0.50, and are marked as "dg" in turn. In Figure c, 2.20, 3.06, 4.32, 7.35 and 7.99ppm are the hydrogens marked as "a", "b", and "c" of LiPSI and the hydrogens on the benzene rings marked as "d", "e", "f" and "g", respectively, where the integration ratio of "a" and "d" is 1.03:1.04, indicating that NaCPSI was successfully grafted onto the polymer backbone and the grafting rate was 100%.
[0057] (3) Preparation of PBI-g-LiPSI doped with zwitterionic MeImPSI material electrolyte membrane
[0058] 1. Thoroughly dry the PBI-g-LiPSI and zwitterionic MeImPSI materials.
[0059] 2. Weigh PBI-g-LiPSI and MeImPSI zwitterionic materials according to the mass ratio of 9:1 to 6:4.
[0060] 3. Add NMP solvent to the stirring tank at a solid content of 15%, add PBI-g-LiPSI and zwitterionic MeImPSI materials, evacuate and heat with stirring at 80°C for 12h until they are completely dissolved into a transparent solution.
[0061] 4. Select a PET release film substrate with a release force of 100 grams and place it on the coating platform. Take out 5 ml of electrolyte slurry and place it on the head end of the PET release film. Complete the slurry coating according to the established coating gap.
[0062] 5. Transfer the coated polymer electrolyte membrane to a vacuum oven and set the baking parameters to 80°C-24h, -1MPa.
[0063] 6. After drying, manually demould to obtain the amphoteric self-supporting single-ion polymer electrolyte membrane.
[0064] (4) Determination of ionic conductivity
[0065] 1. In a vacuum glove box environment, place the punched and dried electrolyte membrane electrode plates in a carbonate solvent and soak them for 2 minutes.
[0066] 2. Assemble the button cell in the order of the negative electrode shell, spring, gasket, diaphragm, gasket and positive electrode shell, wherein a sufficient amount of carbonate solvent is dripped at the interface between the gasket and the diaphragm.
[0067] 3. The assembled button cell was packaged and the ionic conductivity of the diaphragm was measured by the AC impedance test method using the Huachen CHI660E electrochemical workstation.
[0068] The results of the test are shown in Figure 3 , where a and c are the temperature variation curves of the ionic conductivity of the self-supporting single ion membrane with 0% and 25wt% doping ratio; b and d are the lithium ion migration number tested by measuring the relationship between steady-state current and AC impedance. The ionic conductivity of the self-supporting single ion polymer electrolyte membrane tested at different temperatures is plotted against temperature at lgσ-1000 / T to obtain the above chart. The conductivity of the blank reference self-supporting single ion membrane PBI-g-LiPSI is 3.3×10 -4 S cm -1 , 7.7×10 - 4 S cm -1 , 1.6×10 -3 S cm -1 At 25℃, 55℃, and 85℃, the conductivity of the self-supporting single ion membrane PBI-g-LiPSI / MeImPSI (25wt%) is 6.8×10 -4 S cm-1, 1.7×10 -3 S cm-1, 3.8×10 -3 S cm-1 at 25 °C, 55 °C, and 85 °C. It can be seen that with the addition of zwitterion MeImPSI, the ionic conductivity increases significantly.
[0069] In this embodiment, the added reagents such as anhydrous acetonitrile, anhydrous acetone, ether, N-methylpyrrolidone, NN-dimethylacetamide solvent are all of AR grade.
[0070] In this embodiment, the concentration of argon gas used is 99.990% to 99.999%.
[0071] The main purpose of the light-shielding operation adopted in the present embodiments (1) and (2) is to prevent NaI from being oxidized.
[0072] The stirring steps used in this embodiment are all mechanical stirring with a frequency of 300 to 800 Hz.
[0073] In Examples (1) and (2), the yields of the two synthetic products are 90% and 62%, respectively.
[0074] In this embodiment (1), the mass ratio of the zwitterionic material components of PBI-g-LiPSI and MeImPSI is 9:1 to 6:4.
[0075] In this embodiment (3), after the mixed polymer electrolyte slurry is coated and dried, the film thickness can be 5 to 30 um, preferably 15 um.
[0076] In this embodiment (4), the carbonate solvent includes one or more of EC, DMC, DEC, EMC and the like.
[0077] In this embodiment (4), the type of battery used may be CR2016, CR2025, CR2032, etc.
[0078] The above description is only the preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0079] Example 2
[0080] (1) Synthesis of dipole Me2(LiPSI)N(PSI) materials:
[0081] 1. Under argon protection, add 50 mL of anhydrous acetone to a two-necked round-bottom flask wrapped with aluminum foil, followed by 6.23 g (20 mmol) of NaCPSI and 3 g (20 mmol) of NaI.
[0082] 2. The iodine exchange reaction was refluxed at 85°C in the dark for 24 h. After the reaction was completed, the mixture was allowed to stand for 4 h to precipitate sodium chloride. The supernatant was transferred to a single-necked round-bottom flask wrapped with aluminum foil, and the acetone was removed by reduced pressure distillation to obtain NaIPSI.
[0083] 3. Add 60 mL of 40 wt% aqueous dimethylamine hydrochloride solution to the flask containing NaIPSI, stir at room temperature for 24 h, rotary evaporate to remove dimethylamine, add 0.5 M HCl solution to remove impurities, and then rotary evaporate again to remove moisture. Add 50 mL of ethanol to the flask, recrystallize, and filter. Collect the sample. The sample was vacuum dried at 60 ° C overnight to obtain 3-(N, N-dimethylamine)-propanesulfonyl (trifluoromethylsulfonyl) imide (Me2HN(PSI)), with a yield of 80%.
[0084] 4. Repeat the above synthesis of NaIPSI. Dissolve 3.21g (10mmol) Me2HN(PSI) and 0.4g (10mmol) NaOH in 30mL ultrapure water, then transfer to the flask containing NaIPSI and react at 60°C for 72h. After the reaction, rotary evaporate the light yellow solution, filter and wash with anhydrous ethanol and anhydrous methanol in turn. The crude product is dried in vacuo at 80°C to obtain Me2(NaPSI)N(PSI) with a yield of 20%.
[0085] 5. First, immerse 100g of commercial sodium cation exchange resin in a 250mL glass beaker, add 60℃ hot ultrapure water, stir manually with a glass stirring rod for 5 minutes, and then pour out the water. Repeat the washing 5 times to completely remove impurities.
[0086] 6. Pour 1M HCl aqueous solution into the beaker to cover the resin interface, and then stir magnetically at room temperature for 1 hour. Decant the acidic aqueous solution and wash the proton exchange resin with ultrapure water until the pH value is equal to 7. Repeat the proton exchange three times.
[0087] 7. Then pour 1M LiOH aqueous solution into a beaker, seal it on the resin, and then stir it magnetically at room temperature for 1 hour. Decant the alkaline aqueous solution and wash the lithium ion exchange resin with ultrapure water until the pH value is equal to 7. Repeat the lithium ion exchange three times to obtain a lithium ion exchange resin.
[0088] 8. Finally, the lithium cation exchange resin was divided into three different glass beakers. 0.3 g Me2(NaPSI)N(PSI) was dissolved in 50 mL ultrapure water in a glass beaker, and then poured into the glass beaker together with the lithium cation exchange resin and stirred for 1.5 h. The aqueous solution was poured into a second glass beaker containing fresh lithium cation exchange resin and stirred for 1.5 h. Subsequently, magnetic stirring was performed at room temperature for 1.5 h. The aqueous solution was poured into a third glass beaker containing fresh lithium cation exchange resin, and then magnetic stirring was performed for 1.5 h. Water was removed. The crude product was dried at 80 ° C for 12 h and vacuum dried at 80 ° C for 24 h to obtain the final Me2(LiPSI)N(PSI)
[0089] The reaction formula is as follows:
[0090]
[0091] Synthetic material characterization Figure 4 and 5 As shown, Me2(LiPSI)N(PSI) 1 H NMR spectrum ( Figure 4 ), LiCPSI and Me2(LiPSI)N(PSI) 7Li NMR spectrum ( Figure 5 ).
[0092] Me2(LiPSI)N(PSI) 1 H NMR spectra Figure 4 As shown, in addition to the peak of deuterated water, there are four peaks at 3.59, 3.31, 3.11 and 2.32 ppm, corresponding to the hydrogens labeled "m", "i", "k" and "j" in Me2(LiPSI)N(PSI), respectively. The ratio of the peak integrals is 1.00:1.05:1.50:1.00, which is proportional to the number of hydrogens in the chemical structure of Me2(LiPSI)N(PSI).
[0093] Figure 5 The LiCPSI and Me2(LiPSI)N(PSI) 7 In Li NMR spectra, the sharp peak at 0 ppm is the internal reference peak, i.e., the peak of 5 M LiCl dissolved in D2O, and the peak of LiCPSI 7 The peak of Li shifted from 0 to 0.16 ppm, indicating that the electron density outside the lithium nucleus became sparse.
[0094] (2) Synthesis of PBI-g-LiPSI materials
[0095] 1. Take PBI polymer (2 g, 5.144 mmol), add 95 mL of anhydrous N-methylpyrrolidone (NMP), replace with argon three times, heat to 120°C and stir for 12 hours to obtain a light yellow transparent solution after complete dissolution.
[0096] 2. Add 0.35 g of LiH under argon protection and stir at 120°C for 20 h to produce a brown-yellow liquid. Cool naturally to room temperature and mark it as A.
[0097] 3. Take the condenser and 250mL two-necked flask, place them in a 110℃ oven, preheat for 1h, build the device from bottom to top while hot, and wrap it with tin foil. Replace the argon gas 3 times, and after the device is slightly cooled, add 25mL of anhydrous acetone, then add NaCPSI (17.04mmol, 6g), and stir until NaCPSI is completely dissolved.
[0098] 4. Add 90 mL of acetone (slightly turbid), add NaI (54 mmol, 8.1 g), replace with argon three times, reflux at 85°C for 24 h, and protect from light. Cool naturally to room temperature and let stand for B. White substance remains at the bottom.
[0099] 5. Use a syringe wrapped in tin foil to draw the supernatant of B into another 250 mL flask (flask wrapped in tin foil), evaporate the acetone as much as possible in the absence of light, and distill under reduced pressure to obtain NaIPSI.
[0100] 6. Then add A to B, replace with argon three times, heat to 120℃ and react for 72h. Cool naturally. Distill under reduced pressure at 120℃ and concentrate to obtain a dark brown viscous liquid.
[0101] 7. Add an appropriate amount of deionized water. If bubbles are generated, stir to remove excess LiH, then pour into a large amount of acidic (HCl, 1M) aqueous solution, stir until there are no bubbles on the liquid surface, stir ultrasonically, and precipitate a dark brown sample.
[0102] 8. Filter by suction, the filter cake is a dark brown solid, wash three times with water, acidify with (1M) HCl and stir for 72h, dark brown uniform suspension. Filter by suction, wash three times with water, take the filter cake. Lithiation for 12h does not dissolve, and brown solid is obtained.
[0103] 9. Filter with a sand core funnel and dialyze with a dialysis bag for 3 days to remove impurities. Distill under reduced pressure to remove the water solvent, dry at 80°C for 24 hours, and then vacuum dry at 100°C for 24 hours to obtain a brown solid, that is, 3.07g of polybenzimidazole grafted propylsulfonyl (trifluoromethanesulfonyl) imide lithium polymer (PBI-g-LiPSI).
[0104] The reaction is as follows
[0105]
[0106] (3) In-situ film electrode preparation of PBI-g-LiPSI doped with zwitterionic Me2(LiPSI)N(PSI) materials
[0107] 1. Thoroughly dry the PBI-g-LiPSI and zwitterion Me2(LiPSI)N(PSI) materials.
[0108] 2. Weigh PBI-g-LiPSI and Me2(LiPSI)N(PSI) dipole materials according to the mass ratio of 9:1 to 6:4.
[0109] 3. Add NMP solvent to the stirring tank at a solid content of 15%, add PBI-g-LiPSI and dipole Me2(LiPSI)N(PSI) materials, evacuate and heat with stirring at 80°C-12h until completely dissolved into a transparent solution.
[0110] 4. Place the rolled lithium iron phosphate (LFP) electrode flat on the coating platform, take out an appropriate amount of electrolyte slurry and place it at the head of the positive electrode material area, and complete the slurry coating according to the established coating gap.
[0111] 5. Transfer the coated LFP membrane electrode to a vacuum oven and set the baking parameters to 80°C-24h, -1MPa.
[0112] 6. After drying, a membrane electrode sheet with the blended solid electrolyte formed in situ on the surface of the LFP positive electrode can be obtained.
[0113] (4) Button battery assembly
[0114] 1. In a vacuum glove box environment, place the punched and dried LFP / solid electrolyte membrane electrode sheet in a carbonate electrolyte and fully soak it for 2 minutes.
[0115] 2. Assemble the button cell in the order of negative electrode shell, spring, gasket, lithium sheet, membrane electrode, gasket and positive electrode shell, wherein a small amount of electrolyte is added to the interface between lithium metal and membrane electrode to wet the interface.
[0116] 3. Package the assembled button cell and place it in a 45°C temperature environment for 12 hours, then perform cycle testing according to the set charge and discharge conditions.
[0117] The performance test results of button cells with zwitterionic polymer electrolyte membrane electrodes are shown in Figure 6 :(a) Rate performance of PP membrane button cell, (b) Rate performance of membrane electrode button cell; (c) Charge and discharge curves of PP membrane button cell at different rates, (d) Charge and discharge curves of membrane electrode button cell at different rates.
[0118] Depend on Figure 6 a It can be seen that the PP film blank button battery has a specific capacity of 158.7mAh / g at 0.2C, 144.3mAh / g at 0.4C, 134.1mAh / g at 0.6C, 127.6mAh / g at 0.8C, 125.8mAh / g at 1.0C, 111.0mAh / g at 2.0C, and 96.0mAh / g at 3.0C. Figure 6 b It can be seen that for the membrane electrode button cell prepared with zwitterionic polymer electrolyte membrane, the calculated data is 157.2mAh / g at 0.2C, 148.4mAh / g at 0.4C, 144.7mAh / g at 0.6C, 137.5mAh / g at 0.8C, 134.9mAh / g at 1.0C, 119.3mAh / g at 2.0C, and 106.6mAh / g at 3.0C. Figure 6 c and d are the charge and discharge curves of PP diaphragm and membrane electrode button cells at different rates. At the same rate, the zwitterionic polymer has higher ionic conductivity, the voltage gap between the charge and discharge curves is significantly smaller than that of the single-ion conductive lithium battery, and the polarization phenomenon is weakened.
[0119] The above description is only the preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An amphoteric self-supporting single-ion polymer electrolyte membrane, characterized in that: The diaphragm is prepared by physically doping a zwitterionic compound with a self-supporting single ion polymer.
2. The amphoteric self-supporting single-ion polymer electrolyte membrane according to claim 1, characterized in that: The molecular structure of the zwitterionic compound contains two ions of different charges, which are covalently bonded in one molecule and are electrically neutral as a whole. The cations in the zwitterionic molecule include but are not limited to quaternary ammonium or quaternary phosphonium; the anions include but are not limited to The molecular weight of zwitterionic compounds is between 200 and 2000.
3. The amphoteric self-supporting single-ion polymer electrolyte membrane according to claim 1, characterized in that: The molecular structure of the zwitterionic compound is shown in Formula 1 or Formula 2: Wherein R2 is a quaternary ammonium or quaternary phosphonium group, R1, R3 are n1, n2, n3 are 1, 2, 3, 4, 5.
4. The amphoteric self-supporting single-ion polymer electrolyte membrane according to claim 1, characterized in that: The self-supporting single ion polymer is a polymer lithium salt, the main chain of which is polybenzimidazole, polyethylene maleic anhydride, polyethylene, polyamide or polyether, and the side chain is lithium sulfonimide, lithium phosphate, lithium borate or lithium perchlorate.
5. The amphoteric self-supporting single-ion polymer electrolyte membrane according to claim 4, characterized in that: The polymer lithium salt structural formula is:
6. The amphoteric supported ion polymer electrolyte membrane according to claim 1, characterized in that: The mass of the zwitterionic compound accounts for 10% to 40% of the mass of the self-supporting single ion polymer.
7. A method for preparing the amphoteric self-supporting single-ion polymer electrolyte membrane according to any one of claims 1 to 6, characterized in that The following steps are involved: A self-supporting single-ion polymer and a zwitterionic compound are taken into an organic solvent, heated and stirred until completely dissolved, to obtain a uniformly dispersed polymer electrolyte coating slurry; the coating slurry is evenly scraped on the surface of the substrate, and after being fully dried, the electrolyte diaphragm is evenly formed into a film and then demolded to obtain a zwitterionic self-supporting single-ion polymer diaphragm.
8. The preparation method according to claim 7, characterized in that: The organic solvent is anhydrous N-methylpyrrolidone, acetone, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.
9. Use of the amphoteric self-supporting single-ion polymer electrolyte separator according to any one of claims 1 to 6 in a battery.
Citation Information
Cited By
Diaphragm, preparation method thereof and secondary battery
CN121149594A
Diaphragm and method for producing the same, secondary battery
CN121149594B